Safety and efficacy of mTOR inhibitor treatment in patients with tuberous sclerosis complex under 2 years of age - a multicenter retrospective study - Saffari, Afshin; Brösse, Ines; Tilburg, Cornelis M. van; Hoffmann, Georg F.; Kölker, Stefan; Witt, Olaf; Milde, Till; Ziegler, Andreas; Syrbe, Steffen (Orphanet journal of rare diseases, 2019)
Tuberous sclerosis complex (TSC) is a multisystem disease with prominent neurologic manifestations such as epilepsy, cognitive impairment and autism spectrum disorder. mTOR inhibitors have successfully been used to treat TSC-related manifestations in older children and adults. However, data on their safety and efficacy in infants and young children are scarce. The objective of this study is to assess the utility and safety of mTOR inhibitor treatment in TSC patients under the age of 2 years.
Gesehen am 20.09.2019